2002
DOI: 10.1111/1467-873x.00214
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Whiteness and Multicultural Education with Prospective Teachers

Abstract: In this article, I describe how I initiate an examination of whiteness with predominantly white students in teacher preparation programs by the use of group collages-a pedagogical tool that combines visual, textual, and oral representations of subject matter. In doing so, I illustrate one of the ways teacher educators can provide students with opportunities to (1) "see" whiteness as an integral aspect of educational discourse, (2) fix their gaze on themselves as a collective racial group, and (3) engage in pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 20 publications
0
52
0
1
Order By: Relevance
“…Given the persistence of (and recent increase in) racism within Canada and elsewhere it is no longer appropriate to remain polite. Of course, as Kubota (2002) and McIntyre (2002) have noted, politeness stifles meaningful debate within academia and has never really been appropriate in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…Given the persistence of (and recent increase in) racism within Canada and elsewhere it is no longer appropriate to remain polite. Of course, as Kubota (2002) and McIntyre (2002) have noted, politeness stifles meaningful debate within academia and has never really been appropriate in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars suggest the need to interrogate the 'culture of whiteness' in schools and its double hegemonic bind by which racial difference is constructed as a scientific/ natural category and marked as other in relation to whitened norms of neutrality, transparency and universality, assumed to be non-racial (McLaren 1995, Giroux 1997, McIntyre 2002. Posing as an unmarked or invisible category, whiteness thereby facilitates non-ethnic (and uncritical) explanations for enduring educational differentials, usually premised on 'culturalist' differences (Reay et al 2007, Hollinsworth 2014.…”
Section: Inequalitymentioning
confidence: 99%
“…West, 2001), there are several research studies that show the importance of understanding the effects of teachers' racial beliefs in their pedagogical practices (e.g. Arber, 2008;Bergh, Denessen, Hornstra, Voeten, & Holland, 2010;Gere, Buehler, Ballavis, & Haviland, 2009;Greene & Abt-Perkins, 2003;Kubota & Lin, 2006Lewis, Ketter, & Fabos, 2001;McIntyre, 2002;McVee, 2004). Gere et al (2009) showed in their study how different prospective secondary school teachers and researchers encountered and interpreted culturally responsive pedagogy very differently.…”
Section: Introductionmentioning
confidence: 99%
“…According to these researchers, different positions taken by different educators in regards to how they interpreted culturally responsive pedagogy were largely shaped by their raced consciousnesses. Using collage exercises as a medium, McIntyre (2002) examined racial identities of white preservice teachers and showed how their racial identities inform their perspectives of teaching and multicultural education. She concludes that seeing whiteness as the "center stage problem" (p. 46) and focusing on white teachers as a collective racial group will help them engage in the kinds of transformation necessary in working against (as opposed to just talking about) inequality in education.…”
Section: Introductionmentioning
confidence: 99%